Retour sur les origines de l’École des hautes études hispaniques à la lumière des archives personnelles de Pierre Paris - Grégory Reimond (Mélanges de la Casa de Velázquez, 2023)
Our essay proposes to return to an old question, already treated by Antonio Niño and Jean-Marc Delaunay. It concerns the origins of the French Institute of Madrid, in particular its Bordeaux section, the École des hautes études hispaniques (EHEH), which is now one of the two components of the Casa de Velázquez. The sources on which we have worked during our doctoral research, in particular the personal archives of Pierre Paris, provide details on this issue. We will show that an initial project for the creation of a French School in Spain was put forward by Pierre Paris in the summer of 1901 before being put aside a few months later. This project should probably be compared to the one mentioned by Pierre Paris in several later publications, which the Bordeaux professor dates from 1898.